Aspectos do erro humano no contexto da manutenabilidade - estudo de caso: Ponte Rio/Niterói - Gonçalves, Telma Silva (2003)
This study has investigated and analyzed the relationship between man and bis job. The factors that cause or prompt the worker to the error, under the point of view from the health and security, so were approached several knowledge areas , include aspects of ergonomy. Thc invcstigation was done throw thc qualitative research, involving a study of case. The population of this research was the team from the Maintenance Coordination and Conservation of the Concrete Structures , both from lhe Bridge Rio-Niterói. This research aimed was improve the conditions to work in the Bridge, and answer this question: Where is the fault ? In the people or in the environment?